ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BACA SANTRI PADA ERA DIGITAL DIPONDOK PESANTREN DARUL IKHLAS - Atikah, Rahma; Novebri (Fakultas Ilmu Dakwah dan Komunikasi, 2025)
This research aims to analyze the factors that influence students' reading interest at the Darul Ikhlas Islamic Boarding School in the digital era. Students' interest in reading is an important aspect in increasing knowledge and literacy skills, but the presence of digital technology often becomes a significant distraction. This research uses a quantitative approach with a survey method, collecting data through questionnaires distributed to students. Several main factors analyzed include the availability of access to digital information, the role of caregivers and teachers in guiding literacy, the influence of the Islamic boarding school environment, and the tendency to use social media by students. The research results show that easy access to digital content can reduce interest in reading printed books, but the literacy coaching factor from caregivers and teachers has a positive influence in maintaining students' interest in reading. This research recommends the integration of technology in literacy-based learning to increase students' reading interest in the digital era.